ANTISIPASI GEJOLAK SOSIAL DAN PENANGANANNYA - Bambang Rudito (Politeknik Kesejahteraan Sosial, 2004)
The Anticipation of Social Conflict and its Resolution.Social problem usually is interpreted as a criminal problem, or as a common disturbing. In this article, social problem is a cultural lack, when people could not m!erpret the social phenomenon. And this article also explains how the social problem could come a social struggle. And how to detect the social problem through the culture in society.